Telhado verde e sua influência micrometeorológica - SILVA, Renan da Silva e (2019)
In order to minimize the environmental impacts caused by the growing urbanization, the technique of the green roof has been increasingly used. In this sense, this research intends to evaluate the effects of the green roof on its contribution to human thermal comfort in a built environment, based on comfort indexes and analysis of the surface temperature of the roof, through thermographic images. The research was carried out in the Charles Darwin Enterprise Garage Building of the Rio Ave Empreendimentos building in Recife, PE, in two periods, the first without a green roof (2016) and the second with a green roof (2017). Data on air temperature and relative air humidity were recorded externally and internally and precipitation was recorded. Internally the data were recorded in two rooms, one of glass and one of plywood, and the comfort indexes were determined. For the thermal analysis of the cover, thermal images obtained from a thermal camera model FLIR I60 were used. When analyzing the air temperature inside the room with plywood seal, it was verified that without green roof the difference between external and internal temperature was in the order of 2,11 °C (2016), while, after the implantation of the system was 0,82 °C (2017), consequently, it was noticed that the green roof provided environments with indices of comfort more adapted to the human well-being. With the implementation of the green roof there was a reduction in the air temperature and the values of the comfort indexes inside the rooms. As well, as reduction in the external and internal superficial temperature of the coverings, indicating the effectiveness of the use of the vegetation in making a comfortable environment thermally.